2010
DOI: 10.1111/j.1365-2206.2010.00690.x
|View full text |Cite
|
Sign up to set email alerts
|

Aren't they just black kids? Biracial children in the child welfare system

Abstract: In the USA, African‐American children are overrepresented in the child welfare system. However, little is known about the child welfare system experiences of biracial children, who are predominately both White and African‐American. To better understand this population, data from public child welfare in a US county were used to examine biracial children in the child welfare system. Results showed significant racial differences between children in the child welfare system. Despite the common belief that biracial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Hall () stipulates that adopting a more “biracial sensitive practice” should begin by determining “the class, social, and familial circumstances of the client” (p. 38). Despite this call, few studies on mixed‐race populations focus on the challenges of low‐income families (Fusco, Rauktis, McCrae, Cunningham, & Bradley‐King, ) or include groups most at risk for poverty and low‐income status, such as Black‐Hispanics (Romo, ). We argue that research and practice must look most carefully at the ways challenges faced by children in low‐income families combine or perhaps are exacerbated by issues facing multiracial youth and similarly how the experiences of multiracial individuals may engage the difficulties facing poor children and adults.…”
Section: Discussionmentioning
confidence: 99%
“…Hall () stipulates that adopting a more “biracial sensitive practice” should begin by determining “the class, social, and familial circumstances of the client” (p. 38). Despite this call, few studies on mixed‐race populations focus on the challenges of low‐income families (Fusco, Rauktis, McCrae, Cunningham, & Bradley‐King, ) or include groups most at risk for poverty and low‐income status, such as Black‐Hispanics (Romo, ). We argue that research and practice must look most carefully at the ways challenges faced by children in low‐income families combine or perhaps are exacerbated by issues facing multiracial youth and similarly how the experiences of multiracial individuals may engage the difficulties facing poor children and adults.…”
Section: Discussionmentioning
confidence: 99%
“…The current study was motivated by our previous work on racial disparities in referrals to child protective services in an urban county in Pennsylvania. An unexpected finding of the first study was that biracial children were referred to child protective services at 4 times the rate of white children, which was higher than the rate of referral for black children who were 3 times more likely than white children to be referred (Fusco, Rauktis, McCrae, Cunningham & Bradley-King, 2010). Moreover, a significantly higher proportion of biracial children (64%) were rated at moderate to high risk for future child maltreatment because of caregiver age or physical, intellectual, or emotional status, compared with the percentage of African American (44%) and white children (37%) rated at this level of risk.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, little attention has been paid to the experiences of biracial black/white children and their families despite growing evidence that they may also be at risk for negative outcomes. For example, studies in the United Kingdom found black/white biracial children and their mothers to be disproportionately involved in child welfare services (Barn, 1999; Harman, 2010b) as have two studies in the United States (Fusco, Rauktis, McCrae, Cunningham & Bradley, 2010, Fusco & Rauktis, 2012). However, little social work research has been devoted to understanding the experiences of white women who have blurred racial lines by partnering with African American men and having children.…”
mentioning
confidence: 99%
“…There are higher numbers of older African American children in foster care than any other population of children available for adoption (Fusco, Rauktis, McCrae, Cunningham & Bradley-King, 2010). Although there is a preference for infants in adoption practice because many prospective adopters desire to experience all of the stages of childhood, some prospective adopters are motivated to adopt bi-racially or adopt older children because they perceive the children as potentially disadvantaged and sincerely want to improve their lives (Zhang & Lee, 2010;Mallon, 2000).…”
Section: Adoption By a Diverse Populationmentioning
confidence: 99%